Theoretical design of a large effective mode area microstructure optical fiber - Razzak, S.M. Abdur; Namihira, Yoshinori (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
This paper presents a numerical design of a large effective mode area microstructure optical fiber. Using the finite difference time domain numerical simulation method it is shown that the proposed fiber can assume very high effective area of the order 122 to 252 μm2, negative dispersion-flat properties around the 1550 nm wavelength, and very low confinement losses of the order 10–5 dB/km. A hexagonal eight ring silica-air microstructure is used with two air-hole dimensions and a common pitch. A microstructure optical fiber with large effective mode area, low confinement loss, and dispersion-flat property may be promising for next generation optical data transmission applications.
Optica Applicata, Vol. 40, 2010, nr 3, s. 677-683
Keywords: optyka; microstructure optical fiber; large effective mode area; chromatic dispersion